2017
DOI: 10.4103/0366-6999.207474
|View full text |Cite
|
Sign up to set email alerts
|

E-26 Transformation-specific Related Gene Expression and Outcomes in Cytogenetically Normal Acute Myeloid Leukemia

Abstract: Background:The E-26 transformation-specific related gene (ERG) is frequently expressed in cytogenetically normal acute myeloid leukemia (CN-AML). Herein, we performed a meta-analysis to investigate the relationship between the prognostic significance of ERG expression and CN-AML.Methods:A systematic review of PubMed database and other search engines were used to identify the studies between January 2005 and November 2016. A total of 667 CN-AML patients were collected from seven published studies. Of the 667 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Tumor microenvironment (TME) played an important role during neoplasm occurrence and progression [ 16 , 25 , 26 ]. In this study, we calculate the stromal score, immune score, and estimate score in 19 TP53 -mut cancers using the ESTIMATE method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor microenvironment (TME) played an important role during neoplasm occurrence and progression [ 16 , 25 , 26 ]. In this study, we calculate the stromal score, immune score, and estimate score in 19 TP53 -mut cancers using the ESTIMATE method.…”
Section: Resultsmentioning
confidence: 99%
“…The most widely accepted concept is that the nontruncated mutation commonly induces high expression of TP53 [ 13 ]. Previous studies have demonstrated that TP53 mutations are associated with their expression, cancer prognosis [ 13 ], and immune − related research [ 16 ]. Integrated studies combined with these features with classification of TP53 somatic mutation are few.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Moreover, in a meta-analysis of seven studies, it was showed that high ERG expression was associated with lower CR and higher relapse in cytogenetically normal AML patients. 14 ERG was involved in cell differentiation, proliferation and apoptosis. It also plays a role in leukemogenesis as a fusion partner with the FUS gene in recurrent AML patients.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Moreover, ETS-related gene ( ERG ) located on chromosome band 21q22, is a transcription factor required for normal hematopoiesis. 14 The elevated expression of ERG was demonstrated in cytogenetically normal AML patients and has a negative role in the prognosis of AML. 15 , 16 The role of standard treatment in the expression of these genes as well as the effect of post- treatment molecular changes on complete remission (CR) are not clearly investigated in the Iranian population.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic normal acute myeloid leukemia (CN-AML) is considered as a moderate risk AML based on the treatment and cytogenetic classification, and accounts for ~45% of adult AML cases and 20% of pediatric AML cases 7 , 8 . Previous studies have reported that the prognosis of CN-AML can be predicted by identifying mutations in certain genes; for example, NPM1 and CEBPA gene mutations are acquired mutations in CN-AML that have been found to predict a good prognosis 9 - 11 , whereas KIT, RUNX1, IDH1, WT1, FLT3, TET2, ASXL1 and DNMT3A gene mutations are malignant mutations in CN-AML that have been reported to predict a poor prognosis 10 , 12 - 14 .…”
Section: Introductionmentioning
confidence: 99%